MAP-it: a participatory mapping toolkit - Huybrechts, Liesbeth; Laureyssens, Thomas (Leuven/Den Haag Acco, 2012)
MAP-it is a tool for participatory cartography and conversation. It is an open and extendible set of stickers that allows a group of people to make their thoughts explicit about a project, idea, ... in the form of a map. The visual character of mapping allows participants from different backgrounds, who may speak different languages, to discuss and create on equal grounds. MAP-it not only encourages to share positive experiences, but also stimulates critique and debate. This publication will provide the reader with an insight in the tool and the broader field of mapping and methods in participatory design.